2020
DOI: 10.21203/rs.2.21870/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“They have been neglected for a long time”: a qualitative study on the role and recognition of Rural Health Motivators in the Shiselweni region, Eswatini

Abstract: Background: Community health workers (CHWs) are increasingly engaged to address human resource shortages and fill primary healthcare gaps. In Eswatini, a cadre of CHWs called Rural Health Motivators (RHM) was introduced in 1976 to respond to key public health challenges. However, the emergence of health needs, particularly HIV/TB, has been met with inadequate programme amendments; and the role of RHMs has become marginalised following the addition of other CHWs supported by non-governmental organisations. This… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Further, 45% reported a lack of confidence in talking to older women about screening. Our findings mirror previous studies that observed discrepancies in health promotion skills among community health workers in Eswatini (Geldsetzer et al, 2017;Walker et al, 2020) and other African settings (Smith et al, 2014;Glenton et al, 2021). This potentially reflects a weakness in the Swati community health workers' training model (O'Donovan et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Further, 45% reported a lack of confidence in talking to older women about screening. Our findings mirror previous studies that observed discrepancies in health promotion skills among community health workers in Eswatini (Geldsetzer et al, 2017;Walker et al, 2020) and other African settings (Smith et al, 2014;Glenton et al, 2021). This potentially reflects a weakness in the Swati community health workers' training model (O'Donovan et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Eswatini is a lower-middle-income country with a population of 1.2 million. Poverty levels are high at 63%, and 77% of the country’s population resides in rural areas [ 15 ]. The country is divided into four geographic regions namely Hhohho, Manzini, Shiselweni and Lubombo.…”
Section: Methodsmentioning
confidence: 99%